An injectable curcumin-loaded hydrogel for neuroprotective treatment promote nerve tissue repair in rat severe spinal cord injury - Zhang, Zhaoqing; Ma, Haiyan; Tian, Ruisong; Li, Guangwei; Zhao, Fuchang; Xie, Liangyu; Chen, Hao (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSpinal Cord Injury (SCI) leads to severe motor and sensory impairments and underscores the urgent need for the development of effective treatment approaches. The injury microenvironment with oxidation, inflammation and extracellular matrix disruption represents a major barrier to nerve tissue repair as well as the functioning of therapeutic factors.MethodsThis study proposes a curcumin-loaded boronate-crosslinked tannic acid injectable hydrogel (CBT-gel) for effective antioxidants and neuroprotective spinal cord repair. Rat transection SCI models were established, and the CBT-gel was implanted in the injured spinal cord tissue. Behavioral and histological testing was performed to determine the spinal cord repair effects.ResultsThe injectable self-healing hydrogel induced sustainable release of the neuroprotective drug curcumin. The CBT-gel transplantation treatment enhanced axonal preservation and reduced glial scar formation. The results also revealed a reduction in neuroinflammation and cellular oxidative damage.DiscussionThese findings support the potential of CBT-gel to improve the microenvironment for spinal cord repair by leveraging their antioxidant and neuroprotective properties. The results in this study aligns with the documented bioactivity of curcumin, though molecular targets in the CBT-gel treatment require further profiling.